On the sustainability and visibility of medical student journals - Yassar Alamri (New Zealand Medical Student Journal)
First, medical student journals (MSJ) face signi!cant (often unseen) obstacles in remaining a viable endeavour. Second, assuming the journal stands the test of time, its content may not necessarily be visible to the wider audience consuming the medical literature.